Relationship between IL-1β production and endodontic status of human periapical lesions - Popovska, Lidija; Dimova, Cena; Evrosimoska, Biljana; Stojanovska, Vera; Muratovska, Ilijana; Cetenović, Bojana; Marković, Dejan (Vojnosanitetski pregled, 2018)
Background/Aim. Apical periodontitis is mainly caused by bacterial infection within the root canal and periapical bone destruction which are prominent features of this lesion. The aim of this study was to determine the quantity of interleukin-1β in the tissues of periapical lesions and to analyze its relationships with: lesion size, previous treatments and pathohistological finding of involved teeth. Methods. Periapical tissues were obtained from patients undergoing periapical surgery. Out of all 80 cases included in the study, 24 had no previous endodontic treatment (open lesions), 37 were with endodontic failure (closed lesion) and in 15 cases root canal retreatment was performed few months before the surgery. By excluding four samples, the total of 76 samples, consisted of periapical lesions and the apical part of the tooth root, was collected. Each periapical tissue sample was divided into two equal parts. The one half of each lesion was used for quantification of interleukin-1β in tissue homogenates by the enzyme-linked immunosorbent assay (ELISA) method. The other part of each lesion was used for histopathological evaluation. Results. For each of the tissue homogenates, the quantity of interleukin-1β was measured, and it ranged from 0.6 pg/mg up to 74 pg/mg. There was no significant difference between the symptomatology and amount of interleukin-1β. Statistical data analysis showed a moderate correlation between lesion size and interleukin-1β measured values. The highest levels of interleukin-1β corresponded with chronic lesions in the stages of acute exacerbation and granulomas in early developing stages. Persistant granulomas, scar tissues, non-inflamed cysts and teeth with recently finished endodontic treatments showed a significantly lower level of interleukin-1β. Conclusion. The study results suggest that the differences in quantity of interleukin-1β correlate to lesion progression and phases of development.